Electron Microscopic Study of the Effects of Preeclampsia on the Placental Endothelial Cells Ultra Structures during Pregnancy - Kawkab Saleem alkasiy; . May Fadil Al-Habib; Nahidh Addai Abdulshaheed (مجله كليه طب الكندي, 2010)
Background: Preeclampsia occurs in 3-5% of pregnancies and is a major cause (12-20 %) of maternal mortality in developed countries. It is the leading cause of preterm birth and intra-uterine growth restrictions (IUGR). Objective: The study was designed to determine and demonstrate the ultra structural changes of endothelial cells in placenta of women suffering from hypertensive disease. Patients & Methods: Placental samples were obtained from two groups of pregnant women groups (preeclamptic and normal pregnant women). The specimens were fixed in 2.5% gluteraldehyde and preceded for electron microscopic examination. Results: Placenta of women with preeclampsia has shown marked degenerative changes in both endothelial and trophoblastic cells. These changes were represented by precipitation of fibrin with the accumulation of platelets in capillary lumen. Abundance of collagen fibers precipitate in the apical region of both endothelial cells and trophoblasts, with thickening of endothelial basement membrane. Conclusion: All histological changes or lesions obstruct the continuous conduction from maternal surface of the trophoblasts through fetal capillary endothelium causing endothelial dysfunction